The Impact of Occupational Ergonomics on the Prevalence of Low Back Pain in Tailoring Professions: A Systematic Literature Review - Pramesti, Ni Putu Ayu Diah; Firmanto Adi Nurcahyo (HM Publisher, 2024)
Background: Low back pain (LBP) is a prevalent musculoskeletal disorder affecting individuals across various occupations, including tailoring. Tailors often engage in prolonged sitting, repetitive movements, and awkward postures, which can contribute to the development of LBP. This systematic review aims to investigate the impact of occupational ergonomics on the prevalence of LBP in tailoring professions. Methods: A comprehensive search of electronic databases (PubMed, Scopus, Web of Science) was conducted to identify relevant studies published between 2018 and 2024. Studies that examined the relationship between ergonomic factors and LBP among tailors were included. Data extraction and quality assessment were performed independently by two reviewers. Results: A total of 25 studies met the inclusion criteria. The findings consistently demonstrated a significant association between poor ergonomic conditions and an increased prevalence of LBP among tailors. Prolonged sitting, awkward postures, repetitive movements, and inadequate workstation design were identified as key risk factors. Additionally, the review highlighted the positive impact of ergonomic interventions, such as adjustable workstations and training programs, in reducing the prevalence and severity of LBP. Conclusion: This systematic review provides compelling evidence that occupational ergonomics plays a crucial role in the prevalence of LBP among tailors. Implementing ergonomic interventions and promoting proper work practices can significantly reduce the burden of LBP in this population, leading to improved worker health and productivity.